"There is no business on a dead planet” - How and why Finnish food companies engage in biodiversity management and reporting? - Lehtovaara, Katri (2024)
Nature loss is one of the greatest environmental crises of our time, threatening the conditions for life on Earth. The negative impacts of business on nature through global value chains are huge, but companies also have the power to make a difference. In my thesis, I study the biodiversity reporting of Finnish food companies. The aim of the research is to find out to what extent companies disclose biodiversity related information in their external reporting and what are the drivers and motivations of companies and, on the other hand, the difficulties, and hindrances in engaging in biodiversity management and reporting. I use corporate sustainability reports and company interviews as data. The results show that Finnish food companies' reporting on biodiversity is limited and inadequate. Reporting is general, does not include quantitative information on biodiversity impacts and risks, and companies do not have biodiversity targets. Encouragingly, however, interviews show that many companies want to advance in biodiversity management and reporting and set measurable targets. The low level of reporting is at least partly explained by the complexity of biodiversity and the lack of guidance, tools, and expertise in companies to assess biodiversity impacts. To support businesses and accelerate progress, my findings suggest that more cooperation should be initiated between expert organisations and food companies, that companies should direct more resources to sustainability management, in particular biodiversity, and that companies should report more comprehensively to increase transparency, stakeholder awareness and understanding on biodiversity, its significance and businesses impacts on nature.